THE REALITY OF ECONOMIC DEPENDENCY IN MUTHANNA GOVERNORATE FOR THE YEARS 1997 AND 2021 (British Journal of Global Ecology and Sustainable Development, 2023)
The research aims to study economic dependency rates and their impact on the economic development of the population in Al-Muthanna Governorate within its administrative borders in 1997, which was determined by the availability of data resulting from the general population census in 1997, population estimates and the results of the field study for the year 2021, and extracting crude age-dependent and economic dependency rates according to categories. The wide age range as well as the spatial variation at the level of the administrative units in the governorate that the research contained in two sections.The results and analyzes revealed that the population of Al-Muthanna Governorate is young and this youth is directly related to the age dependency ratio, which means a high percentage of the population under (15 years) and its variation at the level of administrative units, in addition to the high real economic dependency rates, as it recorded (106%) in 1997. to (132%) in 2021.